THE PHENOMENON OF CODE-MIXING ON YOUTUBE CASTER OF CLARA MONGSTAR AND RANGER EMAS - Alif Rahmadhani; Desi Arintawati; Fiona Puspitasari Mulyadi; Ginarsiwi Mayangseto; Ratini Setyowati (Universitas Duta Bangsa Surakarta, 2021)
This research on Code-Mixing focuses on language development in the Clara Mongstar and Gold Ranger YouTube videos. The data from this research is the YouTube video of Clara Mongstar and the Gold Ranger in 2020. In addition, the purpose of this research is to find out the use of the language on Youtube. The data collection technique used in this research is descriptive qualitative. Meanwhile, the results found were in the form of the audience's language style from the video they watched. It was found that there were several types of codemixing used by Clara Mongstar in its implementation.